Transient Osteoporosis of the Hip - Nurdan Kotevoğlu; Füsun Şahin; Emel Deniz; Şule Taşpınar; Banu Kuran (Archives of Rheumatology, 2008)
We report two cases which we diagnosed as transient osteoporosis of the hip. We aimed to discuss the steps of diagnosing the disease and importance of different imaging procedures besides presenting the images of healed hip of the first case. Keeping this disease in mind is important during differential diagnosis. (Rheumatism 2008 23: 31-4)